Activation of Group II Metabotropic Glutamate Receptors Suppresses Excitability of Mouse Main Olfactory Bulb External Tufted and Mitral Cells - Dong, Hong-Wei; Ennis, Matthew (Frontiers in Cellular Neuroscience, 2018)
Metabotropic glutamate receptors (mGluRs) are abundantly expressed in the rodent main olfactory bulb. The function of Group I mGluRs has been investigated in a number of studies, while the actions of Group II mGluRs, which include the mGluR2 and mGluR3 subtypes, have been less well explored. Here, we used electrophysiological approaches in mouse olfactory bulb slices to investigate how Group II mGluR activation and inactivation modifies the activity of external tufted (ET) and mitral cells. The Group II mGluR agonist DCG-IV directly and uniformly reduced the spontaneous discharge of ET and mitral cells. The inhibitory effect of DCG-IV was absent in mitral cells with truncated apical dendrites, indicating a glomerular site of action. DCG-IV did not influence olfactory nerve-evoked monosynaptic responses in ET or mitral cells, indicating that Group II mGluRs do not presynaptically modulate glutamate release from olfactory nerve terminals. In contrast, DCG-IV suppressed polysynaptic responses in periglomerular cells evoked by olfactory nerve stimulation. DCG-IV also inhibited glutamate release from ET cells. DCG-IV also suppressed spontaneous and olfactory nerve-evoked long-lasting depolarization in mitral cells. Applied alone, Group II receptor antagonists were without effect, suggesting that basal activation of these receptors is negligible. These findings suggest that Group II mGluRs inhibit ET and mitral cell activity and further dampen intraglomerular excitatory circuits by suppressing glutamate release.